The Reality Of The Policy To Combat Poverty And Unemployment In Algeria - taher, medjahdi; bounouiga, nasira (Journal of Social Sciences and Humanities, 2024)
In essence, This research aimed to give a true picture of the extent of the phenomenon of poverty and unemployment in Algeria, and to highlight the reality of the policies adopted by the state to confront the phenomena of poverty and unemployment, as well as to clarify the nature of the informal sector in Algeria and its impact on the economic and social aspect of society. Through the theoretical and analytical presentation of the research, we found that whenever the problem of poverty and unemployment in Algerian society worsened, successive governments faced it with a set of policies and programs aimed at reducing or at least mitigating them. However, what is recorded on the programs adopted for more than two decades is that most of them remain Unable to solve the problem from its roots in light of the worsening living conditions economically and socially, so it remained mere pacifying programs instead of radical solutions, especially in the field of employment and care for the poor groups, which are called the term disadvantaged groups